Tainted Love: How Stigmatization of a Political Party in News Media Reduces Its Electoral Support. (26th March 2018) - van Spanje, Joost; Azrout, Rachid
Abstract: In contemporary democracies, a political party typically needs good press to attract voters. A glum scenario for a party would be that news media systematically stigmatize it. To what extent does stigmatization lower its electoral support? This article examines voters' reactions to news media coverage of the Dutch party PVV. Using a media content analysis linked to a 2014 panel survey of a sample representative of the Dutch electorate, we find that, among voters who held anti-immigrant attitudes, exposure to stigmatization lowered these voters' perceived legitimacy of the PVV. This, in turn, decreased their propensity to vote for that party. This suggests that stigmatization can be a strong tool in the hands of those who intend to damage a party.